Speaking of the sea in the Azores islands: We sometimes went for lapas - Neilson, Alison Laurie (2015)
This presentation highlights five years of learning from coastal fishing communities in the Azores islands, Portugal. We used photo-elicitation and focus groups to invite people to speak about the sea and all the deep, complex and sometimes contradictory meanings that it may have. The researchers sought environmental justice within the everyday processes using deep ethnographic and autobiographic-narrative inquiry which lead to participation in learning about as well as supporting collaborations between fishers, scientists and policy makers. This work calls for looking at the sea through new eyes, hearing with new ears, feeling differently and awakening to the possibility of knowing the sea in unfamiliar ways